Acquired pyloric stenosis resulting in hypokalaemic, hyperchloraemic normal anion gap metabolic acidosis. Persistent vomiting in an adult: cause and effect. (17th January 2018) - Kaye, Philip
Abstract : A 24-year-old woman presented with a history of persistent vomiting for at least 3 months. This resulted in severe dehydration with risk of acute kidney injury. In addition to volume depletion, loss of gastric fluid resulted in a specific metabolic derangement—hypokalaemic, hypochloraemic normal anion gap metabolic alkalosis with a reduced ionised calcium concentration and paradoxical aciduria. These metabolic changes were reflected in her ECG. Investigation demonstrated acquired gastric outflow tract obstruction secondary to a pyloric peptic ulcer. The patient was resuscitated with intravenous crystalloid and electrolyte supplements. The acquired pyloric stenosis was treated medically with a proton pump inhibitor and Helicobacter pylori eradication therapy with excellent recovery.